Dahi (yogurt) placed within a pot - Mumbai Archive Project Team (Jio Institute, 2024)
The dahi (curd or yogurt) is donated by the villagers and collected in the handi (pot). In its consecrated form, the dahi is a form of prasad (blessed food) that is distributed among the devotees.